Personalized video-based health education after ischemic stroke: A single-center cross-sectional study in China - Jing-Xiu Gao; Mei-Ru Wu; Yi-Tong Chen; Yong-Mei Deng; Chun-Juan Wang; Rui-Hua Ma (PLoS ONE, 2025)
Background and objectives Health education can help patients engage in evidence-based healthy behaviors, and the construction of smart hospitals can promote accurate video-based health education for patients. However, little is known about the clinical practice of personalized video-based health education for ischemic stroke patients in China. We investigated video-based health education viewing frequency and relevant impact factors among patients with ischemic stroke. Methods Data were collected from 1,569 ischemic stroke patients admitted to the Vascular Neurology Ward of a hospital in China between 01/08/2020 and 31/12/2022, to analyze their use of personalized video-based health education. The video-based integrated management system used in our hospital can facilitate keyword extraction, thus achieving accurate and personalized video-based health education and promotion. Data, including demographic and disease-related data, viewing frequency, total viewing amount and viewing frequency for each dimension, were extracted from the hospital’s video integrated management system and medical system. Univariate analysis and multiple linear regression helped identify factors associated with whether the patients viewed personalized video-based health education materials. Results A total of 1569 patients were included (age = 58.72 ± 13.50 years old; 1177 (75.0%) males). Diet rehabilitation education was the most frequently viewed personalized video-based health education dimension; the average viewing frequency was 2.30 ± 1.15 times/day during an average hospitalization of 12.55 ± 4.12 days. According to the multivariable analysis, factors associated with a reduced likelihood of viewing the personalized video-based health education materials (P < 0.05) included visual and hearing impairment, longer hospital stays, and speech impairment. In contrast, compared to self-paying patients, individuals who were covered by medical insurance or received free medical service were more likely to view the personalized video-based health education materials. Conclusion A personalized video-based health education program with a keyword extraction function can help achieve accurate and personalized video-based health education and promotion and effectively improve patients’ health-education participation rate.